2012
DOI: 10.1111/j.1365-2265.2011.04251.x
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of the normal/mild elevated TSH serum levels in children and adolescents with Hashimoto’s thyroiditis and isolated hyperthyrotropinaemia: a 3‐year follow‐up

Abstract: Coeliac disease, elevated TSH and TPOAb at presentation and a progressive increase in TSH are predictive factors for thyroid failure in HT patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
2
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 34 publications
7
87
2
9
Order By: Relevance
“…In the children with HT-related mild SH, it has been just recently reported that the evolution of thyroid function tests seems to be frequently characterized by a deterioration over time, whereas such risk is very low in the children with idiopathic SH (12). However, the available prospective studies on the natural history and prognosis of SH in children are very few and based on 2-3 years follow-up investigations (12,13,14,15,16), which hampers the ability of drawing firm conclusions about the relevance of those findings.…”
Section: Introductionmentioning
confidence: 99%
“…In the children with HT-related mild SH, it has been just recently reported that the evolution of thyroid function tests seems to be frequently characterized by a deterioration over time, whereas such risk is very low in the children with idiopathic SH (12). However, the available prospective studies on the natural history and prognosis of SH in children are very few and based on 2-3 years follow-up investigations (12,13,14,15,16), which hampers the ability of drawing firm conclusions about the relevance of those findings.…”
Section: Introductionmentioning
confidence: 99%
“…In chronic thyroiditis the mean TSH was higher when compared with subjects without thyroid antibodies, regardless of thyroid function. Radetti et al demonstrated that the elevation of TSH levels during follow-up and the progressive increase in thyroid autoantibodies were the strongest predictive factors of future development of thyroid failure in autoimmune thyroiditis patients [35]. The evolution from normal stage to hypothyroidism is a long process, which consequently, after years, provides to hypothyroidism.…”
Section: Prace Oryginalnementioning
confidence: 99%
“…They are summarized in Table 1. Of the nine selected studies, six were longitudinal trials (22,23,25,26,27,29) and three were retrospective (24,28,30). Five were single center studies (22,23,26,27,29) and four were multicenter studies (24,25,28,30).…”
Section: Natural History Of Sh In Children and Adolescentsmentioning
confidence: 99%
“…After reviewing titles, abstracts, and the full-length texts, nine articles were selected for closer assessment and then included in our analysis (22,23,24,25,26,27,28,29,30). They are summarized in Table 1.…”
Section: Natural History Of Sh In Children and Adolescentsmentioning
confidence: 99%